Synthesis and Structure of Cu(II) Azamacrocyclic Complex: Me6[14]N4dieneCu-SCNClO4 - Xia, Hong; Huang, Zi-Xian (Asian Journal of Chemistry, 2010)
A novel copper(II) complex Me6[14]N4dieneCu-SCNClO4, where Me6[14]N4diene is 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazamacrocyclic-4,11-diene, was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal is monoclinic, space group P2(1)/n with unit cell parameters: a = 12.8691(4) Å, b = 11.3306(3) Å, c = 15.7727(5) Å, a = 90º, b = 102.8200(10)º, g = 90º, V = 2242.56(12) Å3, Z = 4, Mr = 501.53, Dc = 1.485 Mg/ cm3, μ = 1.219 mm-1, F(000) = 1052, T = 293(2) K, R = 0.0394, wR = 0.1068 for 16706 reflections with I > 2s(I). The center copper(II) is a five-coordinated in a slightly distorted square pyramidal environment.